INFLUENCE OF INFORMATION SOURCES ON TOURISTS: A CASE STUDY OF STUDENTS OF MARKETING AND MANAGEMENT IN THE SILESIAN REGION - Ochoa, Luis Siguencia; Damian, Herman; Marzano, Gilberto (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This paper presents the results of a field research on the changes that take place in student preferences regarding communication with tourism services, preferences on the ways to search for information sources about place destination and a first  inside about payment forms for tourism and hospitality services.  The study was conducted twice, in 2015 and 2018, among students of tourism management and recreation at the Kukuczki Academy of Physical Education in Katowice and the Banking Higher School in Chorzów.